Instilling Faith and Noble Morals: The Implementation of Tauhid Education at a Madrasah Tsanawiyah - Dadang Zenal Mutaqin; Muhammad Usman Apandi; Jenal Aripin Yusuf; Asep Rusdianto; Tedi Sopyan (AL-ISHLAH: Jurnal Pendidikan, 2025)
Tauhid education aims to instill the belief in the oneness of Allah and the importance of worship. Proper teaching methods are essential to nurturing a generation with strong faith and noble morals. This study explores the learning process at MTs Al-Riyadl Cianjur to develop students with mature faith and high-quality character. This study employs a qualitative descriptive approach, focusing on the tauhid learning model. Data collection involved observations, interviews, and documentation, which were analyzed through data reduction, data presentation, and conclusion drawing. The study found that tauhid education utilizes various teaching methods, including lectures, question-and-answer sessions, discussions, drills, recitations, and uswah (role modelling). The effectiveness of these methods is influenced by supporting factors such as high student interest and teachers’ strong competencies in classroom management. However, challenges include fluctuating student motivation, classroom management difficulties, and limited parental collaboration. Tauhid education is further reinforced through religious practices, such as Dhuha prayer, midday congregational prayer, reciting Al-Asma al-Husna, memorizing selected surahs, reading Juz 'Amma, and celebrating Islamic holidays. These practices strengthen students’ moral and spiritual development. Effective tauhid education relies on appropriate teaching methods, teacher competence, and parental support. Enhancing these aspects can improve students' faith and character, making them more morally and spiritually grounded.